Sensory Pain Qualities in Neuropathic Pain - Mackey, Sean (2011)
The qualities of chronic neuropathic pain (NeP) may be informative about the different mechanisms of pain. We previously developed a 2-factor model of NeP that described an underlying structure among sensory descriptors on the Short-Form McGill Pain Questionnaire (SF-MPQ). The goal of this study was to confirm the correlated 2-factor model of NeP. Individual descriptive scores from the SF-MPQ were analyzed. Confirmatory factor analysis (CFA) was used to test a correlated 2-factor model. Factor 1 (stabbing pain) was characterized by high loadings on stabbing, sharp, and shooting sensory items; factor 2 (heavy pain) was characterized by high loadings on heavy, gnawing, and aching items. Results of the CFA strongly supported the correlated 2-factor model.